Development of Product Innovation in Effort to Increase The Competitiveness of Traditional Products Opak In Opak Centre Tasikmalaya - Nita Fauziah Oktaviani; Evilia Sri Yuniar (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The Cikatuncar Village area, which is located in Kotabaru Village, Cibeureum District, was confirmed as one of the centers of Sundanese traditional food, Opak by the Tasikmalaya Cooperative and MSME, Industry and Trade Office. However, the fact is that the innovations that are owned by the producers are quite minimal in terms of product types and packaging, besides that there are several sales of MSMEs that are dim so that an active effort is needed to help these businesses. One way that can be done is to increase their competitiveness through product innovation. Product innovation that will be carried out in this community services is by developing product through product diversification and also improving the quality of packaging. These product innovations are expected to modernize traditional products so that traditional foods are able to adapt to people's tastes and also expand the existing market, which is expected to boost their income and also increase the income of the surrounding community because some people work for these traditional food producers. The result of this community services is that, our MSME partner produces product and packaging innovations that have never been done before, the response from consumers is very positive, even product and packaging innovations carried out in this community services will continue to be carried out because of the consumer demand that they have.